Proceedings of the 4th International Conference on Frontiers of Educational Technologies 2018
DOI: 10.1145/3233347.3233370
|View full text |Cite
|
Sign up to set email alerts
|

Mutual-Excitation of Cryptocurrency Market Returns and Social Media Topics

Abstract: Cryptocurrencies have recently experienced a new wave of price volatility and interest; activity within social media communities relating to cryptocurrencies has increased significantly.There is currently limited documented knowledge of factors which could indicate future price movements. This paper aims to decipher relationships between cryptocurrency price changes and topic discussion on social media to provide, among other things, an understanding of which topics are indicative of future price movements. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 23 publications
1
29
0
3
Order By: Relevance
“…multiple tokens issued on the Ethereum blockchain). In a related study on topic analysis of tech forums on Reddit [22], authors also find that topics on "fundamental cryptocurrency value" are very frequent in the Ethereum community threads and are correlated with increase in prices.…”
Section: General Remarks For the Bitcoin And Ethereum Analysismentioning
confidence: 94%
See 1 more Smart Citation
“…multiple tokens issued on the Ethereum blockchain). In a related study on topic analysis of tech forums on Reddit [22], authors also find that topics on "fundamental cryptocurrency value" are very frequent in the Ethereum community threads and are correlated with increase in prices.…”
Section: General Remarks For the Bitcoin And Ethereum Analysismentioning
confidence: 94%
“…More broadly, Google search data related to cryptocurrencies can be relevant to characterise the set of Bitcoin users [21]. Temporal topic analysis of Bitcoin and Ethereum discussions on Reddit also show correlations with variations of cryptocurrency prices [22].…”
Section: Introductionmentioning
confidence: 99%
“…The popular modern techniques from Artificial Intelligence and general softcomputing paradigms have been utilized in recent work [89], where price prediction based on historical price values was compared over machine learning with different types of neural networks, and further, in [72], where the sentiment-based prediction of alternative cryptocurrency price fluctuations using a gradient boosting tree model is given. In [105], a mutual-excitation of cryptocurrency market returns and social media topics is investigated, whereas the paper [84] reports a recent study considering the impact of social media on Bitcoin value. Finally, a study measuring the interaction between media sentiment, based on news articles as well as blog posts and the Bitcoin price, is given in [136].…”
Section: Related Workmentioning
confidence: 99%
“…Cryptocurrencies such as Bitcoin assume the role of digital currency. It is not only used worldwide for online payments, but also traded as an investment tool on the market [3]. Therefore, the ability to predict the price volatility of Bitcoin will facilitate payment and investment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kim et al adopted machine learning models to mine user reviews and found that the number of responses to user reviews and online comments affects the number of transactions between users [12]. Peng et al constructed the predictive model by combining SVR and GARCH model [3]. Finally, the performance of SVR-GARCH model is better than GARCH, EGARCH and GJR-GARCH models.…”
Section: Introductionmentioning
confidence: 99%